THE EFFECT OF PRINCIPAL LEADERSHIP AND WORK ENVIRONMENT ON TEACHER PERFORMANCE WITH WORK MOTIVATION - SABUNGAN OMPUSUNGGU (CV KULTURA DIGITAL MEDIA, 2021)
This study aims to determine the Effect of Principal Leadership and Work Environment on Teacher Performance with Work Motivation as an Intervening Variable at SMA Negeri 1 Muara, Muara District, North Tapanuli Regency. This research was conducted at SMA Negeri 1 Muara, Muara District, Muara District in 2017. The population in this study were all 34 teachers, so this study was a population study. The data collection method used a questionnaire. The results showed that the principal's leadership on teacher performance had a value of tcount> ttable (3,065>1,697) and the influence of principal's leadership on work motivation had a value of tcount> ttable (4,966>1,697). This means that the principal's leadership has a positive and significant effect on both teacher performance and work motivation. The results showed that the influence of the work environment on teacher performance had a value of tcount> ttable (2.507> 1.697) and the effect of the work environment on work motivation had a value of tcount> ttable (2.844> 1.697). This means that the work environment has a positive and significant effect on both teacher performance and work motivation. Work motivation has a positive and significant effect on teacher performance, due to tcount> t table (4,197>1,697).